Effects of dopamine depletion on the morphology of medium spiny neurons in the shell and core of the rat nucleus accumbens - Meredith, GE (J Neurosci, 1995)
Nucleus accumbens receives a dense dopaminergic innervation which is important in regulating motivated states of behavior such as goal- directed actions, stimulus-reward associations and reinforcement of addictive substances. The shell and core territories of this nucleus each receive functionally and morphologically distinct dopaminergic inputs and lesions of the ascending pathways totally deprive the core but not the shell of dopaminergic fibers. Medium spiny neurons are the principal targets of dopaminergic terminals. The present study explored whether the loss of dopamine inputs can affect these neurons and whether cells in the shell and core would be equally susceptible to such a loss. Intracellular injection in fixed slices and neuronal reconstruction were used to analyze the dendritic trees of 62 neurons in the shell and core of animals that received a unilateral, chronic 6- hydroxydopamine lesion of the medial forebrain bundle. In the dopamine- depleted core, dendrites are significantly shorter (16% decrease) than in the intact core and in both the dopamine-depleted core and lateral shell, dendrites are less spiny than in respective control regions. Dopamine loss in the medial shell is associated with significantly more tortuous dendrites that are lower in spine density. However, the number of spines is not reduced which may mean that the increase recorded for segment length, although insignificant in tests, could be responsible for the change in spine density. These data suggest that the loss of dopamine can affect accumbal neuronal morphology and, moreover, can affect neuronal structures differentially in the shell and core.